ASSISTANCE TO REALIZE FAMILY HOPE FOR THE IPEMI COMMUNITY, LUBUK BEGALUNG BRANCH - Syahrizal, Syahrizal; Armalena, Armalena; Asril, Asril; Yatim, Yenita; Yuherman, Yuherman; Yulastri, Weni (Universitas PGRI Sumatera Barat, 2024)
The high divorce rate in Padang City is the main concern in a community service program that aims to create a harmonious family through mentoring for members of the Lubuk Begalung branch of the Indonesian Muslimah Entrepreneurs Association (IPEMI). Mentoring involves emotional support, providing knowledge, and skills in identifying and overcoming family problems. This activity is carried out with a participatory and intensive approach, including training and workshops on family hope strategies based on Islamic teachings, which include faith values, prayer implementation, religious education, and family ethics. The implementation method includes needs analysis, work plan, implementation, and evaluation to ensure target achievement. The results of the activity showed an increase in the motivation and enthusiasm of community members in realizing a harmonious family based on Islamic teachings. It is hoped that similar activities can continue to be developed to achieve the goal of family welfare.